ANALISIS PERLAMBANGAN DAN MAKNA KIASAN DALAM ANTOLOGI PUISI LAUTAN ZIKIR KARYA HUSNU ABADI - Dina Komalasari (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2018)
This research is motivated by the fact that in expressing feelings, a poet cannot be separated from the painting of language which is also a tool in obtaining the density of meaning which is a characteristic of a literary work of poetry. The beauty of the language chosen by Husnu Abadi in the anthology of poetry is accompanied by polite and gentle language. Husnu Abadi in conveying something not directly to the object he is aiming for, by analyzing the Mining and Metaphorical Meanings in the Anthology of Ocean Poetry Recitation by Husnu Abadi. This study aims to describe and collect data and analyze about: (1) Mining contained in the anthology of the poetry of Lautan Zikir by Husnu Abadi. (2) The figurative meaning contained in the poetry anthology of Lautan Zikir by Husnu Abadi. The research method used is descriptive method and uses a qualitative approach. Data and data sources in this study are the anthology of Lautan Zikir poetry by Husnu Abadi, published in Pekanbaru by UIR Press in 2004. The number of poems in the poetry anthology is 16 poetry titles and all of them are analyzed. The results showed that the symbolism contained in the anthology of the poetry of the Ocean of the Remembrance symbolizes the similarity in nature to what it symbolizes. In addition, the symbolism in the anthology of poetry and figurative meaning that the author found in the anthology of Lautan Zikir poems by Husnu Abadi, which is dominant, is the style of language or the meaning of equality, allegory, personification, metaphor, hyperbole, totern proparte synekdose, synopsis pars prototo. Besides that, it is also used language style or other classical meanings such as euphemism, irony, and litotes.